Comparative analysis of chickpea with boro rice in drought-prone areas of Bangladesh - Siddique, ST; Kamruzzaman, M; Sharna, SC (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study is conveyed to compare the profitability of chickpea and boro rice in Rajshahi district, which is one of the most drought-prone areas of Bangladesh. In this study, a total of 180 farmers (90 chickpea growers and 90 boro rice growers) are used as sample respondents, and data were collected by using a structured questionnaire in 2019. A probit regression model is used to find out the determinants that affect the cultivation of chickpea and boro rice. The important finding of this study is that the Benefit-Cost Ratio for chickpea and boro rice production is 1.88 and 1.05, respectively. The results indicate that chickpea cultivation is more profitable than boro rice cultivation. Besides, the study reveals that occupation, farm size, and seed have a positive impact while family size, human labor, and irrigation have negative effects on farmer’s decision to cultivate chickpea cultivation rather than boro rice. It is, therefore, concluded that the farmers should be encouraged to grow more chickpea rather than boro rice as a means of increasing farm income through crop diversification program. Int. J. Agril. Res. Innov. Tech. 10(2): 21-28, December 2020